2019
DOI: 10.1093/mnras/stz1255
|View full text |Cite
|
Sign up to set email alerts
|

The mass-loss, expansion velocities, and dust production rates of carbon stars in the Magellanic Clouds

Abstract: The properties of carbon stars in the Magellanic Clouds (MCs) and their total dust production rates are predicted by fitting their spectral energy distributions (SED) over pre-computed grids of spectra reprocessed by dust. The grids are calculated as a function of the stellar parameters by consistently following the growth for several dust species in their circumstellar envelopes, coupled with a stationary wind. Dust radiative transfer is computed taking as input the results of the dust growth calculations. Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
74
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(82 citation statements)
references
References 110 publications
8
74
0
Order By: Relevance
“…Compared with the LMC, the SMC is more deficient in C-AGB stars with thick dust shells. Also Nanni et al (2019) found a group of C-AGB stars with high mass-loss rates in the LMC that is not present in the SMC. This could be because the initial masses of C-AGB stars in the LMC are larger than those in the SMC (Ventura et al 2016).…”
Section: Discussion: Agb Stars In Our Galaxy and The Magellanic Cloudsmentioning
confidence: 93%
See 2 more Smart Citations
“…Compared with the LMC, the SMC is more deficient in C-AGB stars with thick dust shells. Also Nanni et al (2019) found a group of C-AGB stars with high mass-loss rates in the LMC that is not present in the SMC. This could be because the initial masses of C-AGB stars in the LMC are larger than those in the SMC (Ventura et al 2016).…”
Section: Discussion: Agb Stars In Our Galaxy and The Magellanic Cloudsmentioning
confidence: 93%
“…The gas-to-dust ratio (Ψ) is generally estimated to be 50 -200 in our Galaxy (the average Ψ is about 100) and Ψ tends to decrease for a higher metallicity (Draine et al 2007). Nanni et al (2019) found that Ψ is larger in the Magellanic Clouds (Ψ ∼ 700) probably due to the lower metallicity. Figure 12.…”
Section: Infrared Two-color Diagramsmentioning
confidence: 94%
See 1 more Smart Citation
“…A different and complementary approach was followed by Dell'Agli et al (2014a, 2015a, who used stellar evolutionary tracks to characterize the individual sources, in terms of mass, chemical composition and formation epoch of the progenitors, and of the amount and mineralogy of the dust in the circumstellar envelope. Nanni et al (2019) used a similar analysis to derive an estimate of the overall dust production rate by evolved stars in the Magellanic Clouds (hereinafter MC).…”
Section: Introductionmentioning
confidence: 99%
“…A fundamental problem in astrophysics is understanding how stars in the late stages of their evolution enrich galaxies with dust and freshly fused elements. It is currently uncertain what the relative contributions are from the most massive stars, which will explode as supernovae, creating new elements but likely destroying dust, compared to lower-mass stars (e.g., Micelotta et al 2018;Dell'Agli et al 2019;Nanni et al 2019). Low-and intermediate-mass stars create dust grains in the cool outer layers of their atmospheres, and the radiation pressure on these grains then helps drive the mass-loss process (e.g., Höfner & Olofsson 2018; Groenewegen & Sloan 2018, and references therein).…”
Section: Introductionmentioning
confidence: 99%